Case report: Uncommon multiple metastases from occult breast cancer revealed by 68Ga-DOTATATE PET/CT - Hu, Tianyuan; Zhang, Rongqin; Zhang, Bing; He, Shanzhen; Liu, Lian; Zou, Yan; Huang, Junhao; Wang, Bing; Hu, Ping; Zhang, Zhanwen (Frontiers in Oncology, 2023)
Occult breast cancer is an uncommon type of breast cancer and its diagnosis is challenging. It is usually invisible on multiple imaging examines. Metastases to the rectum and inguinal lymph nodes from occult breast lobular cancer are even rarer. 68Ga-DOTA peptides can image neuroendocrine tumors by targeting specific somatostatin receptors. Besides, other tumors, including breast cancer, have been shown to express somatostatin receptors. In this case, we presented a 63-year-old woman who underwent both 18F-FDG and 68Ga-DOTATATE PET/CT due to a rectal polyp. An endoscopic excision biopsy confirmed metastatic carcinoma of suspected breast origin, but subsequent ultrasound and MRI showed no signs of malignancy in the breast and adnexa uteri. PET/CT showed obvious 68Ga-DOTATATE activity in bilateral axillary and right inguinal lymph nodes with mild 18F-FDG uptake. Final histopathology at the left axillary, right inguinal lymph nodes, and rectum indicated metastases from breast cancer while the origin remained radiologically occult. Additionally, one uterine fibroids was found with positive uptake of 68Ga-DOTATATE and negative uptake of 18F-FDG. This case suggested that 68Ga-DOTATAE PET/CT may be an effective supplement in diagnosing OBC lymph node metastases with mild 18F-FDG uptake, and it may provide a new technology for the clinical diagnosis of occult breast cancer.